Insight into the transplacental transport mechanism of methoxylated polybrominated diphenyl ethers using a BeWo cell monolayer model. (October 2020) - Zhang, Xiaolan; Cheng, Xiaomeng; Yu, Yuling; Lei, Bingli; Yu, Yingxin
Abstract: Methoxylated polybrominated diphenyl ethers (MeO-PBDEs), a type of emerging environmental contaminants, can accumulate through the food chain and eventually enter the human body. For pregnant women, these chemicals may be transplacentally transported to their fetuses, causing early intrauterine exposure. This study was designed to explore the transport process and characteristics of MeO-PBDEs using a BeWo cell monolayer model to simulate the placental barrier effect. Concentration-dependent transplacental transport indicates that the transport of MeO-PBDEs may be dominated by passive diffusion within the studied concentration range. According to the apparent permeability coefficients, MeO-BDE congeners investigated can be classified as poorly transported compounds, with the exception of MeO-BDE28. Time-dependent transplacental transport was observed (R 2  = 0.97–0.99), which showed that the intracellular accumulation of MeO-PBDEs followed pseudo-first-order kinetics process. The transport process of MeO-PBDEs in the BeWo cell assay was not found to be sensitive to the pH of 6.5–7.4. An efflux transporter, breast cancer resistance protein, may be involved in the transport process of some MeO-PBDE congeners, and influx transporters, including organic anion transporters and organic cation transporters, may also be involved in the transport process. Although the present results indicated the possible transplacental transport mechanism, more molecular biological studies should be conducted to advance the understanding of the transport mechanisms. Graphical abstract: Image 1 Highlights: Concentration/time-dependent transplacental transport of MeO-PBDEs was observed. Passive diffusion dominated the transplacental transport of MeO-PBDEs. Pseudo-first-order kinetics describe the transplacental transport. The transplacental transport of MeO-PBDEs was not pH sensitive. Some efflux and influx transporters might be involved in the transport. Abstract : Understanding of the transplacental transport process and mechanism of MeO-PBDEs is very important for the assessment of the early life security in humans.